Preoperative Plasma miRNA Levels Predict Prognosis in Early-stage Malignant Melanoma - Bagheri, Mahyar Sharif; Polivka, Jiri; Treskova, Inka; Houfkova, Katerina; Knizkova, Tereza; Woznica, Vlastimil; Fikrle, Tomas; Pivovarcikova, Kristyna; Svaton, Martin; Shetti, Dattatrya; Negi, Rashmi; Pesta, Martin (Anticancer research, 2023)
BACKGROUND/AIM: Non-invasive circulating tumor biomarkers in liquid biopsy, such as microRNAs (miRNA), provide for better personalization of treatment strategies. The aim of our study was to assess the prognosis of patients with melanoma undergoing tumor resection with curative intent based on analysis of selected circulating miRNAs. PATIENTS AND METHODS: A total of 22 patients with stage I to III melanoma were enrolled into this prospective study. Plasma samples were obtained pre-surgery and early post-surgery from peripheral blood draws. A panel of 23 candidate miRNAs was designed and expression of miRNAs were analyzed by reverse transcription-quantitative polymerase chain reaction with exogenous reference control cel-miR-39-3p. RESULTS: Higher preoperative expression levels of miR-99a (p=0.008), miR-320 (p=0.009), miR-1908 (p=0.001), miR-494 (p=0.018) and miR-4487 (p=0.048) were associated with a shorter disease-free interval. Similarly, higher preoperative plasma levels of miR-99a (p=0.017), miR-221 (p=0.026), miR-320 (p=0.016), miR-494 (p=0.009), miR-1260 (p=0.026) and miR-1908 (p=0.024) were associated with worse overall survival. No significant differences between pre- and postoperative plasma miRNA levels were observed. CONCLUSION: Liquid biopsy is a minimally-invasive approach which can lead to a better understanding of cancer behavior and offers the possibility of precise patient prognosis, allowing selection of the most appropriate treatment. Our study showed that preoperative plasma levels of miR-99a, miR-221, miR-320, miR-494, miR-1908 and miR-4487 were associated with disease-free interval and overall survival of patients with early-stage melanoma. This approach may help in decision-making about the appropriateness of modern adjuvant treatment administration in patients with resectable melanoma.
Keywords: mikro RNA; Melanoma; Circulating MicroRNA; stanovení celkové genové exprese; prognóza; nádorové biomarkery; melanom; Gene Expression Profiling; Humans; prospektivní studie; Prospective Studies; cirkulující mikroRNA; MicroRNAs; Prognosis; lidé; Biomarkers, Tumor